Survival analysis of conservative vs. dialysis treatment of elderly patients with CKD stage 5. - Roman Reindl-Schwaighofer; Alexander Kainz; Michael Kammer; Alexandra Dumfarth; Rainer Oberbauer (PLoS ONE)
Elderly patients represent a growing population among people suffering from ESRD. So far only limited data on actual survival benefits of elderly adults initiating dialysis have been published. Besides the high burden of preexisting comorbidities, dialysis treatment itself may be associated with a further deterioration in functional status in this population. We retrospectively analyzed the Austrian Dialysis and Transplant Registry and identified 8,622 patients who started maintenance hemodialysis after the age of 65 years between 2002 and 2009. We compared this data set to a cohort of 174 patients aged over 65 years with CKD stage 5 who progressed to an eGFR < 10ml/min/ and were managed conservatively in the same era. All patients who died of malignant disease were excluded from this analysis. The risk of mortality was analyzed using multivariable Cox proportional hazards models. Furthermore, a parametric model of time to event analysis was used for visualization of changing risk over time and precise calculation of time to equal risk assuming a Weibull distribution. Hemodialysis treatment was associated with a decreased risk for death with a HR of 0.23 (95% CI 0.18 to 0.29; p<0.001) compared to conservative treatment. The time to event analysis however showed, that although survival was initially superior in the hemodialysis group, hazards crossed thereafter. Time to equal risk was 2.9 months and 1.9 months for female and male patient aged 65, respectively, and decreased to one month in the very elderly aged 95. Elderly patients with ERSD did benefit from initiation of hemodialysis, as the conservative group showed a very high initial mortality rate. This survival benefit of dialysis treatment however did not persist beyond the first two months compared to survivors of the conservative group.